2014
DOI: 10.1016/j.otsr.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative lumbar spondylolisthesis. Cohort of 670 patients, and proposal of a new classification

Abstract: IV Observational cohort study. Retrospective review of prospectively collected outcome data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 23 publications
1
32
1
6
Order By: Relevance
“…SL is more common in women (11) . The most common level is L4-L5 (12) . Retrolisthesis is most commonly found in the L3-L4 level, which is a rare condition (11) .…”
Section: Discussionmentioning
confidence: 99%
“…SL is more common in women (11) . The most common level is L4-L5 (12) . Retrolisthesis is most commonly found in the L3-L4 level, which is a rare condition (11) .…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that there was no difference in rates of fusion, operative time, EBL, and ODI, SF-36, and VAS outcome measures between procedures. Similarly, Baker et al completed a more recent systemic review including 13 studies, mostly graded as level III evidence [18,32,[39][40][41][42][43][44][45][46][47][48][49]. The authors concluded that there was not sufficient evidence to recommend for or against interbody fusion.…”
Section: Interbody Fusionmentioning
confidence: 99%
“…It is widely accepted that explicit description of sagittal spine alignment assists in determination of aetiology and the orientation of the surgical plan, both of which are achieved using two incisive tools (spinopelvic parameters and curvatures) in both degenerative spine disease and spine deformity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%